Basidiobolomycosis of the child: clinical aspects in Côte d’Ivoire - Ahogo, K.C.; Azagoh, K.R.; Dou, S.; Kouassi, A.; Allou, A.S.; Kouassi, Y.I. (European Journal of Pediatric Dermatology, 2017)
Few studies are devoted to deep mycoses such as basidiobolomycosis. The objective of this study was to determine the epidemiological and clinical profile and to discuss the treatment of this disease in Côte d’Ivoire. This is a retrospective study over a 21-year period. 20 cases of basidiobolomycosis were diagnosed. Patients’ ages varied from 3 to 15 years with an average of 7 years. The sex ratio was 2 : 1 in favor of the boys. The lesions generally affected the lower limbs. Histopathology and mycology confirmed the diagnosis. Retroviral serology was negative in all patients. Treatment with ketoconazole or itraconazole was instituted with complete cure in 4-6 months. Basidiobolomycosis of the child is a rare condition in Côte d’Ivoire. It is probably under diagnosed. It should be known to all practitioners because its treatment is relatively simple.